Comparison of Mallampati test with lower jaw protrusion maneuver in predicting difficult laryngoscopy and intubation - Muhammad Irfan Ul Haq; Hameed Ullah (Wolters Kluwer Medknow Publications, 2013)
Background: Failure to maintain a patent airway is one of the commonest causes of anesthesia-related morbidity and mortality. Many protocols, algorithms, and different combinations of tested methods for airway assessment have been developed to predict difficult laryngoscopy and intubation. The reported incidence of a difficult intubation varies from 1.5% to 13%. The objective of this study was to compare Mallampati test (MT) with lower jaw protrusion (LJP) maneuver in predicting difficult laryngoscopy and intubation. Materials and Methods: Seven hundred and sixty patients were included in the study. All the patients underwent MT and LJP maneuver for their airway assessment. After a standardized technique of induction of anesthesia, primary anesthetist performed laryngoscopy and graded it according to the grades described by Cormack and Lehane. Sensitivity, specificity, accuracy, and positive predictive value (PPV) and negative predictive value (NPV) were calculated for both these tests with 95% confidence interval (CI) using conventional laryngoscopy as gold standard. Area under curve was also calculated for both, MT and LJP maneuver. A P < 0.05 was taken as significant. Results: LJP maneuver had higher sensitivity (95.9% vs. 27.1%), NPV (98.7% vs. 82.0%), and accuracy (90.1% vs. 80.3%) when compared to MT in predicting difficult laryngoscopy and intubation. Both tests, however, had similar specificity and PPV. There was marked difference in the positive and negative likelihood ratio between LJP and MT. Similarly, the area under the curve favored LJP maneuver over MT. Conclusion: The results of this study show that LJP maneuver is a better test to predict difficult laryngoscopy and tracheal intubation. We recommend the addition of this maneuver to the routine preoperative evaluation of airway.